Febrile Neutropenia Rates According to Body Mass Index and Dose Capping in Women Receiving Chemotherapy for Early Breast Cancer. Issue 9 (September 2016) - Lote, H.; Sharp, A.; Redana, S.; Papadimitraki, E.; Capelan, M.; Ring, A.
Abstract: Aims: Studies suggest worse outcomes in obese women with breast cancer than in non-obese women. One potential reason may be that oncologists 'dose cap' adjuvant chemotherapy in obese patients in order to avoid excessive toxicity. Reductions from standard dosing may compromise survival outcomes in the curative setting. Here we describe the body mass index (BMI) distribution of patients in a non-trial population, the frequency with which oncologists dose cap and its effect on febrile neutropenia chemotherapy toxicity. Materials and methods: In this non-randomised study, electronic patient records retrospectively identified patients with early breast cancer who initiated neoadjuvant or adjuvant chemotherapy at the Royal Marsden Hospital between 1 January and 31 December 2013. Baseline data included age, BMI, performance status, tumour characteristics, granulocyte colony-stimulating factor and comorbidities. Chemotherapy doses, rates of dose capping across BMI groups and rates of febrile neutropenia were reported. Results: In total, 325 patients were eligible: 79 (24.5%) were obese (BMI ≥ 30), 109 (33.5%) were overweight (BMI ≥25 – <30) and 137 (42%) were normal bodyweight (BMI < 25). Sixteen patients (20.5%) in the obese group received dose-capped chemotherapy. Overall, 62 patients (19%) had an episode of febrile neutropenia. Obese patients receiving uncapped chemotherapy did not experience a significant difference in febrile neutropenia rates when compared with overweight or normal bodyweight groups ( P  = 0.5798). The febrile neutropenia rate in obese patients receiving capped chemotherapy was 6.5%, compared with 24% in obese patients receiving uncapped chemotherapy ( P  = 0.1216). Conclusion: In a non-trial population of obese patients, dose capping is frequently used. Obese patients receiving uncapped chemotherapy do not experience increased febrile neutropenia rates when compared with uncapped overweight or normal bodyweight patients. Furthermore, dose capping was associated with a trend towards lower rates of febrile neutropenia than in other groups and may indicate relative under-dosing of chemotherapy. This supports international guidelines that state that obese patients should not be dose capped. Highlights: Dose capping is frequently observed in obese patients. Obese patients receiving uncapped chemotherapy do not experience increased febrile neutropenia rates. Dose capping is associated with a trend towards lower rates of febrile neutropenia than other groups. As per ASCO guidelines: obese patients should not be dose capped.